Relationship among levels of leptin and zinc, copper, and zinc/copper ratio in plasma of patients with essential hypertension and healthy normotensive subjects - Canatan, H; Bakan, I; Akbulut, M; Halifeoglu, I; Cikim, G; Baydas, G; Kilic, N (Springernature, 2004)
Obesity is among the main contributing factors in the etiology of essential hypertension (EHT). Leptin, the product of the ob gene, is expressed mainly in adipose tissue. We examined the relationship between two trace elements, zinc (Zn) and copper (Cu), and leptin in patients with EHT (n=35) and normotensive (NT) controls (n=50) because leptin as well as Zn and Cu were reported to be associated with the pathophysiology of EHT. Plasma leptin levels were determined with a commercial enzyme-linked immunosorbent assay (ELISA) kit. Atomic absorption spectrophotometry was utilized to determine plasma Zn and Cu levels. There was a negative correlation between leptin and Zn, and the Zn/Cu ratio (r= -0.359, p<0.05; r= -0.361, p<0.05, respectively) in pooled subjects. When subjects were divided based on the presence or absence of hypertension, there was a negative correlation between leptin and Zn (r= -0.375, p<0.05) as well as leptin and Zn/Cu ratio (r= -0.398, p<0.05) in NT subjects. Similar trends were observed when leptin/BMI (body mass index) levels were utilized. There was no significant correlations between levels of Cu and leptin or leptin/BMI. In conclusion, in addition to high leptin levels, Zn and the Zn/Cu ratio were lower in patients with EHT compared to NT controls.
Keywords: leptin; zinc; copper; hypertension